Production, purification and characterization of a minor form of xylanase from Aspergillus versicolor - Carmona, E. C.; Fialho, M. B.; Buchgnani, E. B.; Coelho, G. D.; Brocheto-Braga, M. R.; Jorge, J. A. (Elsevier B.V., 2005)
A strain of Aspergillus versicolor produces a xylanolytic complex containing two components, the minor component being designated xylanase II. The highest production of xylanase II was observed in cultures grown for 5 days in 1% wheat bran as carbon source, at pH 6.5. Xylanase II was purified 28-fold by DEAE-Sephadex and HPLC GF-5 10 gel filtration. Xylanase II was a monomeric glycoprotein, exhibiting a molecular mass of 32 kDa with 14.1% of carbohydrate content. Optimal pH and temperature values for the enzyme activity were about 6.0-7.0 and 55 degreesC, respectively. Xylanase II thermoinactivation at 50degreesC showed a biphasic curve. The ions Hg2+, Cu2+ and the detergent SDS were strong inhibitors, while Mn2+ ions and dithiothreitol were stimulators of the enzyme activity. The enzyme was specific for xylans, showing higher specific activity on birchwood xylan. The Michaelis-Menten constant (K-m) for birchwood xylan was estimated to be 2.3 mg ml(-1) while maximal velocity (V-max) was 233.1 mumol mg(-1) min(-1) of protein. The hydrolysis of oat spell xylan released only xylooligosaccharides. Published by Elsevier Ltd.
Keywords: Aspergillus versicolor; xylanase; endoxylanase; enzyme purification